SONOGRAPHIC EVALUATIONS OF THE EFFECTS OF MATERNAL GESTATIONAL DIABETES ON FETAL GROWTH AND DEVELOPMENT DURING THIRD TRIMESTER OF PREGNANCY: - Riaz, Muqaddas; Badar, Rimsha; Sheikh, Danial Hanan; Inam, Sidra; Zafar, Sidra (Annals of Allied Health Sciences, 2025)
Objective: To determine the role of ultrasound in detecting congenital abnormalities in fetus complicated with maternal gestational diabetes. Material & Methods: A retrospective study was conducted on patients presenting with gestational diabetes mellitus at Fatima Memorial Hospital Shadman, Lahore. The study was conducted from August 2024 to December 2024. The sample size was 59. A self-designed proforma was used for data collection. Women with gestational diabetes, aged 18-45 years, were included in this study. Results: Mean age of participants was 32 years with age range 18 to 45 years. 40 (67.79%) were detected with fetal congenital abnormalities. Out of these 40 patients, 13(32.5%) were found to have macrosomia, 4(10%) were found to have growth restriction, 7(17.5%) were found to have fetal death, 2(5%) were found to have respiratory distress syndrome, and 14(35%) were found to have premature baby. Conclusion: Ultrasound is the best imaging modality in the diagnosis of fetal congenital abnormalities in patients with maternal gestational diabetes mellitus complication.